Pemanfaatan Media Pembelajaran Berbasis Teknologi sebagai Alat Pembelajaran Kekinian bagi Guru Profesional IPS dalam Penerapan Pendidikan Karakter Menyongsong Era Society 5.0 - Eni Rahayu Widyawati; Sukadari Sukadari (Proceedings Series on Social Sciences & Humanities, 2023)
The writing of this article aims to (1) find out the optimal use of technology-based learning media as a contemporary learning tool for social studies professional teachers; (2) explore the utilization of technology-based learning media as a contemporary learning tool in implementing students' character education; (3) identify the roles and challenges of social studies professional teachers in utilizing technology-based learning media as a contemporary learning tool in students' character education towards the Era of Society 5.0. The method used in writing this article is descriptive qualitative, employing a literature review approach to collect relevant data from various academic sources such as books, journals, magazines, brochures, websites, and other references related to the topic of "The Optimal Use of Technology-Based Learning Media in Contemporary Social Studies Education for Character Development Towards the Era of Society 5.0." The literature review was conducted between mid-March and early April 2023, focusing on selecting recent academic works published between the years 2018 to 2023. The purpose of this research method is to synthesize and analyze existing literature to gain insights into the utilization of technology-based learning media in character education within the context of contemporary social studies education and its relevance in preparing students for the challenges of Society 5.0. The results of writing this article show that; (1) The optimal use of technology-based learning media as a contemporary learning tool for social studies professional teachers can lead to faster and significant scientific contributions in the field of science and technology for the advancement of national education. (2) Technology-based learning media as a contemporary learning tool in student character education has the potential to create a character-based, moral, and culturally enriched educational landscape that preserves and promotes local cultural wisdom. (3) To identify the roles and challenges of social studies professional teachers in utilizing technology-based learning media as a contemporary learning tool in student character education in welcoming the Society 5.0 Era. Indeed, as a facilitator in the learning process, a teacher's role goes beyond just delivering content. They play a crucial role in guiding and supporting students, evaluating their progress, and encouraging continuous skill development. In the context of technology-based learning applications and the challenges brought forth by the Era of Society 5.0, teachers must possess information and technology literacy to effectively integrate technology into their teaching practices. To produce students who are active, creative, innovative, and think critically, educators must adopt a learner-centered approach and implement effective teaching strategies.Â